A Novel L-Gate InGaAs/GaAsSb TFET with Improved Performance and Suppressed Ambipolar Effect - Boyang Ma; Shupeng Chen; Shulong Wang; Tao Han; Hao Zhang; Chenyu Yin; Yaolin Chen; Hongxia Liu (Micromachines, 2022)
A heterojunction tunneling field effect transistor with an L-shaped gate (HJ-LTFET), which is very applicable to operate at low voltage, is proposed and studied by TCAD tools in this paper. InGaAs/GaAsSb heterojunction is applied in HJ-LTFET to enhance the ON-state current (ION). Owing to the quasi-broken gap energy band alignment of InGaAs/GaAsSb heterojunction, height and thickness of tunneling barrier are greatly reduced. However, the OFF-state leakage current (IOFF) also increases significantly due to the reduced barrier height and thickness and results in an obvious source-to-drain tunneling (SDT). In order to solve this problem, an HfO2 barrier layer is inserted between source and drain. Result shows that the insertion layer can greatly suppress the horizontal tunneling leakage appears at the source and drain interface. Other optimization studies such as work function modulation, doping concentration optimization, scaling capability, and analog/RF performance analysis are carried out, too. Finally, the HJ-LTFET with a large ION of 213 μA/μm, a steep average SS of 8.9 mV/dec, and a suppressed IOFF of 10−12 μA/μm can be obtained. Not only that, but the fT and GBP reached the maximum values of 68.3 GHz and 7.3 GHz under the condition of Vd = 0.5 V, respectively.